Comparison of pest management practices between highland and lowland vegetable farmers - Azuwa, Nurzawani (2014)
Vegetable production is seen as one of the important food productions in Malaysia, with total production of 874,602 tonnes in 2011. In ensuring only safe fresh food is being produced, it is crucial to understand the pest practices management practices among vegetable farmers in Malaysia There are two types of area for vegetable productions that can be found in Malaysia, which are lowland area and highland (temperate) area. A survey with 147 of vegetable farmers in Johor, Pahang, Selangor, Perak Negeri Sembilan and Kedah have been conducted to understand the influence of highland and lowland farming on pest management practices. The number of respondents varied in every district and random sampling method. Structured questionnaire which include background of the study, status of pest and disease incidence, type of pesticides use, pesticides application technique and pest management practices have been developed and used for face-to-face interviewed. All the data was analyzed using the SPSS statistical software (Version 16.0). Farmers in lowland and highland area have similar practices, therefore, there is no significant different in their pest management practices. From the result, it was identified that the respondents in both area depended on chemical pesticides for the management of pest and diseases. Farmers in both areas usually used 3–4 types of pesticide to control the pest over a season and moderately toxicity pesticides are commonly used. Most farmers mentioned that extension officer did not gives much help in giving guidance on the use of pesticides and they do not understand very well about Integrated Pest Management (IPM). Eventually, the objectives of keeping food safe fresh produce can be achieved if there is involvement of all parties in vegetable crops and improving IPM methods.